Synthesis of polymer network scaffolds from L-lactide and poly(ethylene glycol) and their interaction with cells - Han, DK; Hubbell, JA (AMER CHEMICAL SOC, 1997)
New lactide-based poly(ethylene glycol) (PEG) polymer networks (GL-PEGs) have been prepared by UV photopolymerization using two nontoxic macromers, triacrylated lactic acid oligomer emanating from a glycerol center (GL) and monoacrylated PEG. These materials have been developed for use as polymer scaffolds in tissue engineering, which have cell-adhesion resistant, ligand-immobilizable, and biodegradable characteristics. The GL-PEG cross-linked polymer networks obtained were glassy and transparent, and the gel content was approximately 90%, irrespective of the degree of polymerization of lactide on the glycerol center and the amount and molecular weight of the PEG acrylate incorporated. All networks showed relatively low swelling in water, due to their highly cross-linked nature. They had no melting endotherms, but they displayed glass transition temperatures indicative of phase-mixing of the PEG. Analysis by ESCA, contact angle measurement, and cell culture indicated the presence of PEG at the network surfaces and showed that higher molecular weight PEG was incorporated into the network surfaces to a higher extent, rendered the surfaces more hydrophilic, and repelled cell adhesion more effectively than did PEG of lower molecular weights. All GL networks showed much less adhesion and spreading of human foreskin fibroblasts than glass used as a control: In particular, GL-PEG networks were highly resistant to cell adhesion due to the mobile PEG chains. Given that the terminal hydroxyl function on the incorporated PEG can be readily derivatized with a bioactive peptide, these degradable networks should be useful as polymer scaffolds for tissue engineering.
Keywords: SURFACE-PROPERTIES; POLYURETHANES; ADHESION; PEO; POLYDEPSIPEPTIDES; THROMBOGENICITY; BIOMATERIALS; FIBRONECTIN; TRIACRYLATE; COPOLYMERS